The concept of Communicative Intention in Speaking models - Wiater, Aleksander (Papers in Linguistics, 2019)
This article presents the current state of studies of Speaking Models conducted by researchers interested in the process of speech language production. The author presents different types of Speaking Models appropriate for first language speakers, bilingual speakers and for learners involved in the process of second language acquisition. He focuses on the role of the Communicative Intention in the Speaking Models. Some of them do not include it explicitly, in others this intention emerges during the conceptualisation phase. However, the importance of this first stage of cognitive stimulus in speech production gives sufficient evidence to emphasise the role of this concept in all current speaking models.